A Growth Model Forecast of Faculty Size and Salaries in United States Higher Education - Porter, Richard C. (The Review of Economics and Statistics, 1965)
ONE of the principal inputs in the process of producing higher education is past higher education. In order to turn out individuals with university degrees, it is necessary that some of the past recipients of such degrees shall have chosen to join university faculties. The recognition that university graduates are the output of higher education, that faculties are the capital stock, and that the hiring of recent graduates to faculties is the investment process, permits the future growth of higher education in the United States to be analyzed within a Harrod growth framework. Although other concepts are needed even at a high level of abstraction, the capital-output ratio (i.e., the faculty-student ratio) and the investment-output ratio (i.e., the ratio of increments of higher education faculties to past recipients of degrees), are central to this analysis of higher education. The essential difference between this paper and typical growth models is that output in higher education is here treated as a parameter rather than a variable. It is possible that the pressures of rapidly increasing applications to institutions of higher education might result largely in increasing rejections, but the more likely course is the expansion of existing universities and the establishment of new ones.' The purpose of this paper is to show the kinds of pressure and the extent of the pressure which may appear in American higher education as a result of various plausible enrollment rates between now and 1980.2 In the growth model of this paper and the forecasts that result from it will be seen the tremendous strain which the next decade will probably place upon American universities and colleges. What is interesting is not, of course, the existence of this strain long ago realized by educators but the measures of its depth and duration. If the faculty investment rate is not increased, faculty-student ratios will very probably fall by 23% (from .089 to .069) between 1957-1958 and 1967-1968. But the very process of producing this vastly increased amount of higher education produces a greatly increased potential later rise of faculties. After 1967-1968, again if the faculty investment rate remains unchanged, faculty-student ratios will begin to rise almost as dramatically as they fell and will re-attain levels above .08 by 19791980. The strain on faculties during the 1960's tends automatically to reduce this strain in the 1970's and possibly to produce slack thereafter. If faculty salaries adjust to prevent, at least partially, these strains and slacks, faculty pay may nearly double during the next two decades, but the rise will not be smooth. Salaries may rise by 7 % per annum during the 1960's but only by 1% per annum in the 1970's. The financial future of those who profess in higher education may be neither so stable nor so bright as is commonly believed.